Tissue Chromogranin A Expression during Prostate Cancer Progression: Prediction of Chemosensitivity - Mitsui, Yozo; Arichi, Naoko; Hiraki, Miho; Harada, Yuji; Yasumoto, Hiroaki; Shiina, Hiroaki (Urology Journal, 2015)
Purpose: We investigated the clinical significance of chromogranin A (CgA) expression as a neuroendocrine (NE) marker during prostate cancer (PCa) progression, especially as a potential predictor of chemotherapeutic response in castration-resistant PCa (CRPC) patients based on immunohistochemical findings. Materials and Methods: Sixteen CRPC patients who underwent combination (docetaxel/estramustine/ carboplatin; DEC) chemotherapy were retrospectively studied. Immunostaining of CgA was performed using prostate biopsy samples obtained at the initial PCa diagnosis, during androgen deprivation therapy, at the time of CRPC diagnosis, and after 2 cycles of DEC therapy. The positive rate was expressed as the mean percentage of positively stained tumor cells against the total number of tumor cells. Differences in positive rates among the treatment courses were compared using a Mann-Whitney test. Results: The mean percentage of CgA-positive PCa cells increased in a stepwise manner until CRPC development and then significantly decreased after DEC therapy. Subanalysis of CgA at CRPC diagnosis showed a more evident reduction of CgA expression after DEC therapy in patients who also had a high level of CgA as compared to those with a low CgA level (P = .003). Likewise, longer prostate-specific antigen progression-free survival was related to CRPC and high CgA (P = .028). Conclusion: NE differentiation of PCa cells is accelerated despite androgen deprivation and reaches a peak at the time of CRPC diagnosis. Although further studies using larger samples are needed, CgA expression in CRPC may be a candidate tissue biomarker to reflect the chemotherapy sensitivity of individual PCa cells.